How does bias correction impact simulated drought characteristics by Regional Climate Models? - Phuong Nguyen-Ngoc-Bich; Manh-Hung Le; Tan Phan-Van; Thanh Ngo-Duc; Tuan Tran-Bui-Anh; Long Trinh-Tuan; Huong Ngo-Thi-Thanh; Dat Pham-Tien; Fredolin T. Tangang; Liew Juneng; Faye Cruz; Jing Xiang Chung; et al. (Climatic Change, 2025)

Rapid, complex back barrier pedestal formation preconditions washover deposition on the southeast Indian coast - Chris Gouramanis; Seshachalam Srinivasalu; Andasabari Karthik; Dat T. Pham; Stephen Carson; Adam D. Switzer (Marine Geology, 2025)

Assessing meteorological trends and variabilities in major river basins of Northern Vietnam using global datasets - Binh Quang Nguyen; Manh-Hung Le; Trong Dieu Hien Le; Tu Hoang Le; Dat Le Tan Nguyen; Hung T. Pham; Doan Van Binh; Hong Xuan Do (Theoretical and Applied Climatology, 2025)

A new circulation in glycolysis of polyethylene terephthalate using MOF-based catalysts for environmental sustainability of plastic - Duong Dinh Pham; Dat-Nguyen Vo; Mai Thanh Phong; Huu Hieu Nguyen; Trung Nguyen-Thoi; Thuy-Phuong T. Pham; Duy Ha Le Phuong; Le Kim Hoang Pham; Da Hye Won; Dang Le Tri Nguyen; Tung M. Nguyen (Chemical Engineering Journal, 2024)

Innovative method for rice straw valorization into nanocellulose, lignin and silica - Tuyen B. Ly; Nhi T.T. Tran; Co D. Pham; Dat D.B. Nguyen; Phong T. Mai; Phung K. Le (Bioresource Technology Reports, 2024)

Sea-level trends and variability along the coast of Vietnam over 2002–2018: Insights from the X-TRACK/ALES altimetry dataset and coastal tide gauges - Dat T. Pham; William Llovel; Truong M. Nguyen; Huy Q. Le; Minh N. Le; Huong T. Ha (Advances in Space Research, 2024)

Effect of Gradient Descent Optimizers and Dropout Technique on Deep Learning LSTM Performance in Rainfall-runoff Modeling - Duong Tran Anh; Dat Vi Thanh; Hoang Minh Le; Bang Tran Sy; Ahad Hasan Tanim; Quoc Bao Pham; Thanh Duc Dang; Son T. Mai; Nguyen Mai Dang (Water Resources Management, 2023)

Icariin reduces bone loss in a Rankl‐induced transgenic medaka ( Oryzias latipes ) model for osteoporosis - Cuong V. Pham; Thanh T. Pham; Thuy T. Lai; Dat C. Trinh; Huong V. M. Nguyen; Tam T. M. Ha; Thuong T. Phuong; Long D. Tran; Christoph Winkler; Thuy T. To (Journal of Fish Biology, 2021)
Given the limitations and side effects of many synthetic drugs, natural products are an important alternative source for drugs and medications for many diseases. Icariin (ICA), one of the main flavonoids from plants of the Epimedium genus, has been shown to ameliorate osteoporosis and improve bone health in preclinical studies. Those studies have used different in vivo models, mostly rodents, but the underlying mechanisms remain unclear. The present study shows, for the first time, that ICA reduces bone damage in a Rankl‐induced medaka fish ( Oryzias latipes ), a non‐rodent osteoporosis model. Live imaging was previously performed in this model to characterize antiresorptive and bone‐anabolic properties of drugs. Here, a new quantification method (I M ) was established based on the length of mineralized neural arches to quantify levels of bone mineralization damage and protection in early post‐embryonic fish. This method was validated by quantification of three levels of bone damage in three independent Rankl fish lines, and by the determination of different degrees of severity of osteoporosis‐like phenotypes in one Rankl line exposed to variable Rankl induction schemes. I M was also used to quantify the efficacy of alendronate and etidronate, two common anti‐osteoporotic bisphosphonates, and revealed comparable bone protective effects for ICA and alendronate in this fish osteoporosis model. This study's data support the value of the medaka fish model for bone research and establish a method to screen for novel osteoprotective compounds.

Spatiotemporal variations of extreme sea levels around the South China Sea: assessing the influence of tropical cyclones, monsoons and major climate modes - Dat T. Pham; Adam D. Switzer; Gabriel Huerta; Aron J. Meltzner; Huan M. Nguyen; Emma M. Hill (Natural Hazards, 2019)

Bioeconomics of mud crab, Scylla paramamosain , culture in Vietnam - Elizabeth H. Petersen; Truong H. Phuong; Nguyen Van Dung; Pham T. Giang; Nguyen K. Dat; Vu A. Tuan; Tran V. Nghi; Brett D. Glencross (Reviews in Aquaculture, 2013)
The results of bioeconomic analysis informed by a survey of 80 small‐scale mud crab farmers in Vietnam are presented in this paper. Mud crab farming in Vietnam is profitable, with net revenue being approximately 135 and 41 million VND/year (USD 7000–USD 2100 per year) in the central and southern regions, respectively. Profitability was significantly higher in the centre compared with the north, as almost three times the biomass is harvested in the centre compared with the south (in turn, due to higher aquaculture area and survival rates). The benefit–cost ratio (the ratio between total revenue and total costs) is 3.55 in the centre and 1.97 in the south. The crabs are fed almost exclusively on low‐value finfish in the centre and the south. Feeding rates were found to be low, with 95% of biomass gain coming from natural feed in the environment rather than supplementary feeding by the farmer. If pellets are to be adopted widely by mud crab farmers, negative perceptions regarding the poor adaptability of mud crab to pellets (northern farmers only), relatively slow growth rates compared with low‐value finfish and lack of availability of pellets need to be overcome.